Global trends in the clinical utilization of exosomes in dermatology: a bibliometric analysis - Tang, Shiqin; Cai, Pai; He, Huina; Tian, Yanan; Hao, Ruiying; Liu, Xin; Jing, Tingting; Xu, Yanyan; Li, Xiaojing (Frontiers in Medicine, 2024)
The arena of exosomal research presents substantial emerging prospects for clinical dermatology applications. This investigation conducts a thorough analysis of the contemporary global research landscape regarding exosomes and their implications for dermatological applications over the preceding decade. Employing bibliometric methodologies, this study meticulously dissects the knowledge framework and identifies dynamic trends within this specialized field. Contemporary scholarly literature spanning the last decade was sourced from the Web of Science Core Collection (WoSCC) database. Subsequent to retrieval, both quantitative and visual analyses of the pertinent publications were performed utilizing the analytical software tools VOSviewer and Citespace. A comprehensive retrieval yielded 545 scholarly articles dated from January 1, 2014, to December 31, 2023. Leading the research forefront are institutions such as Shanghai Jiao Tong University, The Fourth Military Medical University, and Sun Yat-Sen University. The most prolific contributors on a national scale are China, the United States, and South Korea. Among the authors, Zhang Bin, Zhang Wei, and Zhang Yan emerge as the most published, with Zhang Bin also achieving the distinction of being the most cited. The International Journal of Molecular Sciences leads in article publications, whereas Stem Cell Research & Therapy holds the pinnacle in citation rankings. Theranostics boasts the highest impact factor among the periodicals. Current research hotspots in this area include Adipose mesenchymal stem cell-derived exosomes(ADSC-Exos), diabetic skin wounds, cutaneous angiogenesis, and the combination of biomaterials and exosomes. This manuscript constitutes the inaugural comprehensive bibliometric analysis that delineates the prevailing research trends and advancements in the clinical application of exosomes in dermatology. These analyses illuminate the contemporary research focal points and trajectories, providing invaluable insights that will inform further exploration within this domain.